Dynamic, Not Isometric Resistance Training Improves Muscle Inflammation, Oxidative Stress and Hypertrophy in Rats - Neves, Rodrigo Vanerson Passos; Rosa, Thiago Santos; Souza, Michel Kendy; Oliveira, Alexsander José Costa; Gomes, Gustavo Neves Souza; Brixi, Bernardo; Souza, Luiz Humberto Rodrigues; Deus, Lysleine Alves; Simões, Herbert Gustavo; Stone, Whitley Jo; Prestes, Jonato; Moraes, Milton Rocha (Frontiers in Physiology, 2019)
This study aimed to compare the effects of dynamic (DRT) and isometric (IRT) resistance training on blood glucose, muscle redox capacity, inflammatory state, and muscle strength and hypertrophy. Fifteen 12-week-old male Wistar rats were randomly allocated into 3 groups: control group (CTL), DRT and IRT, n = 5 animals per group. The animals were submitted to a maximal weight carried (MWC; every 15 days) and maximum isometric resistance (MIR; pre- and post-training) tests. Both training protocols were performed 5 times a week during 12 weeks, consisting of 1 set of 8 uninterrupted climbs for 1 min with a 30% overload of MWC. The animals in the IRT group remained under isometry for 1 minute. The DRT group experienced greater MWC from pre to post-training compared to the CTL and IRT groups (p<.0001). The DRT and IRT groups displayed similar gains in MIR (p=.3658). The DRT group exhibited improved glycemic homeostasis (p=.0111), redox (p<.0001), and inflammatory (p<.0001) balance as compared with CTL and IRT groups. In addition, the improved glycemic profile was associated with an increase in muscle strength and hypertrophy, improvement in redox balance and inflammation status. We conclude that DRT was more effective than IRT on increasing cross-sectional area, but not muscle strength, in parallel to improved blood glucose, inflammatory status, and redox balance.